2004
DOI: 10.1002/ijc.20730
|View full text |Cite
|
Sign up to set email alerts
|

hOGG1 Ser326Cys polymorphism and G:C‐to‐T:A mutations: No evidence for a role in tobacco‐related non small cell lung cancer

Abstract: Human 8-oxoguanine DNA glycosylase 1 (hOGG1) plays a major role in the repair of 8-hydroxyguanine, one of the major forms of DNA damage generated by reactive oxygen species in tobacco smoke. If left unrepaired by hOGG1, 8-hydroxyguanine can produce G:C-to-T:A transversions. Recent studies have suggested that the hOGG1 Ser326Cys polymorphism is associated with both a decrease in enzyme activity and an increased risk of lung cancer. To define the interaction between tobacco carcinogens, hOGG1-mediated DNA repair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 36 publications
0
10
1
Order By: Relevance
“…No difference in catalytic activities was observed between the hOGG1 326C and hOGG1 326S alleles in several studies [4046]. However, the hOGG1 encoded by the wild-type 326S allele exhibited higher DNA repair activity than the hOGG1 326C variant in other studies [38, 4750]. …”
Section: Resultsmentioning
confidence: 94%
“…No difference in catalytic activities was observed between the hOGG1 326C and hOGG1 326S alleles in several studies [4046]. However, the hOGG1 encoded by the wild-type 326S allele exhibited higher DNA repair activity than the hOGG1 326C variant in other studies [38, 4750]. …”
Section: Resultsmentioning
confidence: 94%
“…However, a biological function of hOGG1 Ser326Cys polymorphism was not supported, as the hOGG1-Cys variant was not associated with p53 mutation in patients with lung cancer. 30 This discrepancy may have been due to the predominant influence of APE1 on the DNA glycosylase activity of hOGG1. In the present study, we consistently found that the hOGG1 Ser326Cys polymorphism was not associated with p53 mutation in the present population; however, p53 mutation was significantly more frequent in participants who had hOGG1-Cys alleles plus the APE1 Asp/Asp genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, hOGG1 Ser326Cys polymorphism, commonly observed in lung cancer, has been shown to reduce hOgg1 enzyme activity, suggesting that this polymorphism plays an important role in the risk for lung cancer (Kohno et al, 1998;Wikman et al, 2000). However, the contribution of the Ser326Cys polymorphism to lung cancer remains controversial as other studies suggested that there may be no association of this polymorphism with the risk of lung cancer development, and further that the contribution of Ser326Cys to lung cancer risk may be different among different geographic populations (Wikman et al, 2000;Vogel et al, 2004;Hu and Ahrendt, 2005). Further studies are needed to assess the importance of the interpopulation variation to cancer susceptibility.…”
Section: Discussionmentioning
confidence: 99%